A Multi-scale Inversion Method Based on Convolutional Wavelet Transform Applied in Cross-Hole Resistivity Electrical Tomography. Issue 1 (February 2021) - Pang, Yonghao; Liu, Zhengyu; Wang, Ning; Nie, Lichao; Wang, Huaihong
Abstract: With the increasing demand for fine exploration, there is also a growing demand on the use of the cross-hole electrical resistivity tomography (ERT). However, the boundaries of geological bodies cannot be accurately described when traditional smooth constraint method was adopted. To solve this problem, we studied a multi-scale inversion method based on convolution wavelet transform. The finite element method is used in the modeling process. The imaging effects of numerical simulation are discussed, such as a single rectangular target, two rectangular targets, Irregular targets, and layered models. The effectiveness of multi-scale methods in cross-hole ERT has been revealed in this work.